OPTIMALISASI PERAN MAHASISWA SEBAGAI STAKEHOLDER DALAM PENGAWASAN PARTISIPATIF MENUJU PILKADA KOTA PADANG TAHUN 2024 - Angggraini, Dewi; Sari, Lusi Puspika; Tamrin, Tamrin; Ramadhon, Azkiya Putri; Saputra, Doni (Ensiklopedia Sosial Review, 2025)
Abstract: Participatory oversight plays a crucial role in monitoring the implementation of Local Head Elections (Pilkada) to ensure that the electoral process adheres to the principles of democracy. In the context of electoral oversight, the institution responsible for supervising the democratic process in Indonesia is the General Election Supervisory Agency (Bawaslu). Bawaslu collaborates with lecturers from Universitas Andalas to enhance the role of the youth in participatory oversight, involving students from the university through a qualitative approach with a descriptive method. The focus is on seminars aimed at educating students about their important role as stakeholders in participatory oversight during local elections.The initiative significantly improves students' understanding of their roles as active and participatory voters ahead of the 2024 Pilkada. Participants experience substantial knowledge gains regarding the electoral system and the significance of participatory oversight. Through the material presented, students grasp the fundamental concepts of local elections, the functions of voters, and current issues related to elections, such as electoral bribery and the neutrality of civil servants. This is reflected in the positive changes in participants' understanding. The seminar plays an essential role in optimizing students' positions as stakeholders in participatory oversight, with sessions that provide deeper insights into their roles and concrete ways to contribute. The campus oversight declaration symbolizes students' commitment to being more actively involved in election supervision. Collaboration with Bawaslu also yields positive outcomes, strengthening students' capacities and the relationship between academia and electoral oversight institutions.Keywords: Participatory Oversight, Regional Elections, Role of Students.